(untitled) (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
This study covers the design and optimization for the on-grid renewable micro-grid network with solar photovoltaic energy, battery storage system, inverter, and grid interconnectivity, all with a view to efficiently tackle the energy requirements while viewing sustainability. A few configurations were analyzed in this study by using HOMER simulation software so that this paper could present the most cost-effective and reliable solution against the base-case of the government incentivized LCOE of the Turkish national power grid. The optimal architecture: 11,841 kW solar photovoltaic; 6,162 kW converter with grid interconnection-at net present cost of 2.69M to realize an LCOE of 0.01111/kWh. Then, the percentage of renewable penetrations would come to about 82.8%, reducing the environmental impact by the reduction in the carbon dioxide emissions by more than 50%, without sacrificing operational reliability. Economic analysis for these types of solar-powered net-metered systems shows huge savings from the base case of only-grid use: 14.1% IRR, simple payback in 6.7 years, and a discounted payback period of 8.85 years. The analysis of energy production per month shows very clearly that this kind of system is perfectly able to satisfy fully day-to-day demand but with some excess energy returned to the grid. The research work hereby establishes the technical and economic viability of the renewable energy microgrid system in efficient and sustainable power generation.